GAMBARAN KETRAMPILAN SOSIAL ANAK REMAJA YANG MENGALAMI GANGGUAN PERILAKU - Pujiani, Pujiani (Jurnal EDUNursing, 2018)
Social skills for a child are important factors to start and have a positive social relationship. Lack of social skills in a child can cause difficulties in adjusting to the surrounding environment, so that children become inferior, isolated from society, tend to behave less normatively, even more extreme such as mental disorders, juvenile delinquency, crime and violence. The purpose of this study to investigate the social skills of adolescents who experience behavioral disorders. This type of research uses descriptive. The study population was children who experienced behavioral disorders in MAN 5 Jombang. The sampling technique is purposive sampling. Research variables are social skills of adolescents who experience behavioral disorders. Data collection from respondents using a question sheet. The social skills questionnaire was prepared based on the Skill and Problem Scales of Preschool and Kindergarten behaviors scale, which was modified according to the needs of researchers. Data analysis is carried out using frequency distribution, percentage and average values for each variable. The results of the study found that the social skills of adolescents who experienced behavioral disorders were low. This is influenced by several factors including gender, parent's work, family's socioeconomic status, parent's education, number of siblings and family form. School can work together with the Ministry of Religion and parents to improve children's social skills so they realize how to instill good education for the future of children.Keywords: social skills, behavioral disorders, adolescents